A Feasibility Study on Cement Bonded Particle Boards with Recycled Expandable Polystyrene Component - Arceo, Ethel (College of Engineering, 2001)
Wallite, a cement-bonded particle board made from polystyrene packaging provides one of the answers to our country's environmental problem. Wallite is manufactured from the familiar and simple raw materials of cement, cement binder and recycled polystyrene packaging. Wallite has a wide range of uses primarily in paneling and construction purposes. They can be used specifically as wall paneling for interior and exterior walls, as ceilings, and as partitions/dividers. Aside from these, the product can also be used in furnishings and any other non-load bearing applications. and any other non-load bearing applications. Market opportunity analysis indicates that there is sufficient demand for the product is analyzed from the projected growth of private and public construction. From the market segmentation performed, it was decided that the target market shall include the National Capital Region, Region III and Region IV focusing on potential customers belonging to the middle and lower income classes. The product shall be available in size 4x8, in three varying thickness: 1/2", 1/4", and 3/4". It will be initially be available in one standard color, white, as preferred by most customers. Being a new product in the market, concentrated efforts shall be put forth on promotions in order for the buying population to become aware that an excellent substitute for construction materials exists. The product can be featured in public service television shows as well as trade fairs, newspapers and radio programs. . Wholesale distribution of the product shall be employed. A ten-year production plan is prepared and cost-estimates are based on these forecasted data. All raw materials shall be acquired locally from suppliers evaluated based on a set of criteria.The polystyrene packaging shall be provided by a single supplier, the Polystyrene Packaging Council of the Philippines. The production process is composed of relatively few operations requiring heavy and especially designed equipment. A rough estimate of 21 employees shall be employed to carry out the administr5ation and production processes. The facilities shall be housed in a warehouse where all the operations will be carried out. After thorough evaluation, the chosen site for the plant is Guiguinto, Bulacan. The total project cost was estimated to be around P6.5 M. In order to finance the project, a corporate form of organization shall be adopted based on the fact that a corporation provides a relatively immediate way of pooling for investments. Sensitivity analysis and different financial measures were performed and from these the project is proven to be a profitable venture and is capable to service its obligations. Lastly, qualitative and quantitative cost and benefit analysis were performed in order to assess the social profitability of the venture. The project's benefits such as its environment friendliness. affordability for the end-user, taxes paid to the government, generation of jobs, far outweighs its lone cost of high water consumption. Taken as a whole, the market, technical, financial and social profitability analysis performed, the project is confirmed to be feasible.